CORRECTION OF RETINAL ANGIOPATHY OF HYPERTENSIVE TYPE BY MINOXIDIL, SILDENAFIL IN EXPERIMENT - Anna Peresypkina; Viktoriya Gubareva; Elena Levkova; Anna Shabelnikova (Belgorod National Research University, 2016)
For the study of retinoprotective properties of pharmacological agents a model of retinal angiopathy of hypertensive type was created against the background of N-nitro-L-arginine methyl ester (L-NAME) administration in a dose 12.5 mg/kg rat body weight for 28 days. We studied the retinoprotective effects of minoxidil in a dose 0.5 mg/kg, sildenafil in a dose 0.5 mg/kg and distant ischemic preconditioning (DIP) on a model of retinal angiopathy of hypertensive type in Wistar rats. The experiment showed that minoxidil in a dose 0.5 mg/kg prevented the development of ischemic damage and retinal vascular changes of hypertensive type caused by the introduction of L-NAME for 28 days, to a greater extent than sildenafil and distant ischemic preconditioning. The observed retinoprotective effects are confirmed by ophthalmoscopy, laser Doppler flowmetry (LDF) and electroretinography (ERG). The lack of positive dynamics in experimental groups with the introduction of glibenclamide in a dose 5 mg/kg confirms the key role of ATP-dependent potassium channels in the mechanism of realization of preconditioning. Detection of preconditioning properties of pharmacological agents may be a new approach in the correction and prevention of retinal angiopathy, which is the initial part of hypertensive retinopathy.